(untitled) (Journal of the College of Education for Women, 2019)
Violence can be identified as an outreaching on others’ dignity,freedom, properties, and life. Therefore, violent actions cannot be determinedonly on materialistic attacks such as killing, beating, robbery, rape, and civilwars, but it also includes the verbal attacks such as insult, threat, and cursing.Violence against women can be identified as any bad actions that aredone against women, which lead to a physical or psychological harm, andinvade their safety and freedom whether these actions come from men orwomen, against one woman or a group of women in special and generalplaces.Before, the social, historical and lawful manners concentrated onsexual distinction between the men and a woman, which, later on, leads to awomanish revolution in the sixties of the last century. This produced aninternational womanish movement that aimed to destroy focusing onmasculinity in society.This research includes eight chapters. The first chapter deals with theconceptual and methodical framework. Chapter two is about the past studies.While chapter three deals with violence against women as a violation tohuman rights. Chapter four talks about what human beings inherit from socialtraditions that strengthen violence against women. Then in chapter five, we have the types of violence and its different and famous forms in societies. Inchapter six there is analysis to the reasons of violence. While chapter seventalks about violence in Iraq. And finally, there is a practical study whichincludes a list of information applied on five women who are molested toviolence and visit Al- Karkh court. Also, in this research, I depended on themethod of case study, where I have chosen five cases of women who sufferfrom violence from different regions in Baghdad. Their case shows howfamily violence humiliates woman and subjects her to man’s authority,without having any social and legislative protection to protect woman insociety.